How does a network of Colombian interethnic women foster resilience to climate change and contribute to gender equality? - Howland, Fanny Cecile; Salas, Daniela (CGIAR System Organization, 2024)
Despite the growing demand for improved intersectional integration of gender in agricultural policies (McDougall et al., 2022), the integration of gender and intersectionality (G&I) considerations into climate change (CC) policy cycles in Latin America has been overlooked. Climate and gender policies are generally formulated with a top-down approach without integrating the knowledge, perceptions and demands of women and men (Howland et al., 2021) and do not address the structural causes of gender inequalities, leading to inadequate policy formulation.